Assemblages of Social Wasps (Hymenoptera, Vespidae, Polistinae) in the Veredas of Central Brazil - de Castro, Lourivaldo Amancio; Andena, Sergio Ricardo; Anjos e Silva, Evandson José (Sociobiology, 2021)
Social wasps are widely distributed in Brazil, and their distribution is intimately linked to habitats and the vegetation structure. Veredas (Brazilian Palm swamps) occur in moist soils and are characterized by the almost monodominant presence of Buriti palms (Maurítia flexuosa). The insect fauna of these environments is poorly known, especially in Central Brazil. Some studies assessing the diversity of social wasps were carried out in the State of Mato Grosso, however, there are no studies performed in the palm swamps of this region. Thus, we aim in this study to investigate the composition of wasp species in six vereda environments throughout 24 months of sampling, from august 2017 to July 2019; The specimens were collected using a sweep net, in 200m transects that were subdivided into 10 3m2 parcels. To attract the wasps, we sprayed each parcel (using a backpack sprayer) with an insect attractant made from five spoons of granulated sugar and one spoon of salt dissolved in 5 liters of water. After spraying the plot, we waited 10 minutes before starting the collections and stayed another 10 minutes to sample in each plot, totaling 200 minutes of sampling per palm swamp. A total of 1062 social wasp specimens were collected, distributed in 10 genera and 36 species. The most abundant species were Polybia cf. ruficeps xantops (Richards, 1978), Angiopolybia pallens (Lepeletier, 1836), Polybia rejecta (Lepeletier, 1836), and Mischocyttarus sp. 2, which accounted for 57% of the total collected specimens in the 60 parcels. The estimated richness for the Vereda environments was 38,88 ± 0,627, approximately 41% of the 88 species of Polistinae wasps found in the Cerrado of eastern Mato Grosso.